2015
DOI: 10.1155/2015/948262
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Anti-Inflammatory Activity of the Extracts of the African Medicinal PlantXimenia caffra

Abstract: A method was developed for identification and quantification of polyphenols in the leaves of Ximenia caffra using HPLC/UV/MS. Based on analyzing the MS and UV data and in comparison to the authentic standards, a total of 10 polyphenols were identified and quantified, including gallic acid, catechin, quercetin, kaempferol, and their derivatives. The total content of these compounds was found to be approximately 19.45 mg/g in the leaf and the most abundant is quercetin-rutinoside (9.08 mg/g). The total phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…As part of documentation of medicinal plants used in Namibia, Zhen et al reported that local herbalists in Namibia use the leaves and roots of Ximenia caffra for various disease conditions. 51 For instance, extracts from the leaf of X. caffra has shown anti-inflammatory activity. To evaluate the effect of X. caffra leaf extract on the LPS-stimulated expression of inflammatory enzymes and pro-inflammatory cytokines, the mRNA expressions of inflammatory markers lL-6, inducible nitric oxide synthase (iNOS), and TNF-α were measured by qPCR.…”
Section: Medicinal Plants With Anti-inflammatory Activities From Counmentioning
confidence: 99%
“…As part of documentation of medicinal plants used in Namibia, Zhen et al reported that local herbalists in Namibia use the leaves and roots of Ximenia caffra for various disease conditions. 51 For instance, extracts from the leaf of X. caffra has shown anti-inflammatory activity. To evaluate the effect of X. caffra leaf extract on the LPS-stimulated expression of inflammatory enzymes and pro-inflammatory cytokines, the mRNA expressions of inflammatory markers lL-6, inducible nitric oxide synthase (iNOS), and TNF-α were measured by qPCR.…”
Section: Medicinal Plants With Anti-inflammatory Activities From Counmentioning
confidence: 99%
“…However, inflammation may cause diseases such as heart disease, diabetic, cancer, and arthritis [114]. This issue can be overcome by consuming a diet which includes flavonoids and phenolic compounds that possess antioxidant activities [115]. Plant extracts isolated from the Middle East region have exhibited anti-inflammation and anti-diabetic properties, which aid in enhancing the immune system of the host.…”
Section: Anti-inflammation and Anti-diabetic Activitymentioning
confidence: 99%
“…It grows in dry woodland and wooded grassland, often on rocky hillsides [7,8]. The fruits from the tree are picked and eaten raw after ripening, and refreshing juice can be prepared by squeezing fruits in water and adding sugar [7,9]. It has been reported that X. caffra has a potential medicinal use by the local communities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that X. caffra has a potential medicinal use by the local communities. The leaves are used as a remedy for malaria, coughs, toothache, stomach-ache, ulcers and hookworm while roots are also used as a cure for infertility, mental illness, bilharzia, scorpion bites, menstrual problems, anaemia, hernia and intestinal worms [9,10]. Several studies confirmed that large numbers of medicinal plants are also good free radical scavengers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation